Efeitos da aplicação de revestimento de quitosana e óleo essencial de orégano no controle da qualidade pós-colheita em tomates cereja - Barreto, Tainá Amaral (2016)
Cherry tomato (Lycopersicon esculentum L.) fruit are higly perishable. The infection of cherry tomato fruit with the pathogenic fungi Aspergillus niger and Rhizopus stolonifer is associated with high postharvest losses and decreased quality during storage. This study evaluated the efficacy of an edible coating comprising chitosan (CHI; 4 mg/mL) and Origanum vulgare L. essential oil (OVEO; 1.25 μL/mL) for keeping the quality of cherry tomato fruit during storage at room (25 °C; 12 days) and cold (12 °C; 24 days) temperatures, considering the physical, physicochemical and sensory aspects. The minimum inhibitory concentrations (MIC) of CHI and OVEO were 4 mg/mL and 10 μL/mL respectively, against R. stolonifer and A. niger. The incorporation of CHI 4 mg/ml and OVEO 5 μL/mL, 2.5 μL/mL and 1.25 μL/mL in the growth media showed fungicidal effect and strongly inhibited the germination of spores, mycelial growth and sporulation of fungal strains test. CHI-OVEO coating reduced black mold and soft-rot incidence caused by these fungi in artificially contaminated cherry tomato fruit during storage at both temperatures. Fruit coated with CHI-OVEO showed higher firmness and lower weigth loss. CHI-OVEO coating delayed the decrease of lycopene, ascorbic and citric acid, glucose and fructose during storage at room or cold temperatures. Fruit coated with CHI-OVEO showed increased amounts of catechin, myricetin, caffeic and syringic acids at the end of storage. CHI-OVEO coating is a feasible treatment for keep the storage quality of cherry tomato fruit. These results indicate that the CHI-OVEO edible coating is a viable treatment for maintaining quality during storage cherry tomatoes.